Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3109/02713683.2011.635916
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo, In VitroToxicity andIn VitroAngiogenic Inhibition of Sunitinib Malate

Abstract: Sunitinib malate 12.5 mg/ml caused no toxicity in in vivo and in vitro models, but the 25 mg/ml concentration caused retinal changes suggesting toxicity in the in vivo model. Further research with the drug is needed in models of ocular neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In an ocular toxicity study on sunitinib, 30 the authors reported that no toxicity related to sunitinib was observed using an in vitro model of HUVEC and ARPE cell cultures after treatment with 12.5 and 25 mg/mL solutions (25-fold and 50-fold the concentrations used for topical treatment in our study). No toxicity was induced in the in vivo model of intravitreal injection after treatment with 12.5 mg/mL (1.25 mg/ 0.1 mL, 5-fold the concentration administered to the subconjunctival group in our study).…”
Section: Discussionmentioning
confidence: 64%
“…In an ocular toxicity study on sunitinib, 30 the authors reported that no toxicity related to sunitinib was observed using an in vitro model of HUVEC and ARPE cell cultures after treatment with 12.5 and 25 mg/mL solutions (25-fold and 50-fold the concentrations used for topical treatment in our study). No toxicity was induced in the in vivo model of intravitreal injection after treatment with 12.5 mg/mL (1.25 mg/ 0.1 mL, 5-fold the concentration administered to the subconjunctival group in our study).…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, in comparison with our study, they had used greater dose intervals. Dib and co-workers evaluated in vivo and in vitro toxicity of sunitinib malate, a multi-kinase inhibitor [33]. In the in vivo model, 0.1 cc of sunitinib was injected intravitreally in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Further trials with longer periods of follow-up will be necessary to address this point. In our study, doses of sunitinib malate were drastically decreased from the previous reports, mainly to minimize the ocular toxicity associated with sunitinib malate[25] and also to establish an objective comparison between the angioinhibitory effects of the bevacizumab versus the corrected values of sunitinib malate. The controversy in sunitinib malate dosage for the optimal CNV treatment is not ignorable and mandates further studies to elucidate the optimal dosage.…”
Section: Discussionmentioning
confidence: 99%